Pengaruh Mixing Eyeshadow Glitter dengan Highlighter untuk Ketahanan Warna Eyeshadow pada Rias Pengantin Sunda Siger Modifikasi - Dewi Safitri; Mitra Lusiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Sundanese Siger bridal makeup is widely modified in terms of makeup that looks simple and soft. One important part of bridal makeup is the eyes. For cosmetics in eye makeup, namely eyeshadow. In addition to eyeshadow, Highlighter can also be used as eyeshadow. The function of Highlighter on the eyes is to provide a shimmer effect and make the eyeshadow color more durable. The purpose of this study was to see the effect of applying mixing glitter eyeshadow with Highlighter for the durability of eyeshadow color in Sundanese Siger bridal makeup.modification. The method used is pre-experimental with a quantitative approach. The number of samples is six people with three control groups and three experimental groups. The sampling technique is purposive sampling. Data analysis techniques consist of normality tests, homogeneity tests and hypothesis tests. The results show that the application of mixing glitter eyeshadow with Highlighter produces 61% smoothness, 66% evenness, and 33% durability. Statistical analysis shows no significant effect on three indicators, namely smoothness p = 1,000, evenness p = 0.527, and durability p = 0.834. It is hoped that this research can provide insight that the Sundanese Siger modified bride can still create an elegant and magnificent impression without glitter and Highlighter, and emphasize the importance of harmony between traditional and modern elements in makeup.